Sabah Feminist Novelists: Views of Their Own: (Novelis Feminis Sabah: Sudut Pandangan Mereka) (Malay Literature, 2021)
This paper scrutinizes five award-winning novels by five Sabah female writers and the issues of sexual discrimination, lack of opportunities, patriarchal hegemony and the negative perceptions of the body that plague Sabah Malay women. A discursive analysis of these issues is anchored upon a gynocritic feminist approach first introduced by Elaine Showalter in her famous essay entitled "Toward a Feminist Poetics" (Newton, 1997). The purpose of this study is to uncover the concept of the feminine "self" in the Sabah context through a thirty-year interrogation represented by these five female authors' novels and narrative styles, which include an exploration of their themes, language styles and poetics through the five novels entitled Malisiah by Obasiah Hj Usman (1986), Dari dalam Cermin by Azmah Nordin (1992), Gadis Adikara by Ruhaini Matdarin (2007), Pagi di Hujung Senja by Kathirina Susanna Tati (2013) and Helaian Linangkit by Dayangku Mastura Pg. Ismail (2016).